Prevalence of Australians exposed to potentially cardiotoxic cancer medicines: a population-based cohort studyResearch in context - Benjamin Daniels; Maria Aslam; Marina T. van Leeuwen; Martin Brown; Lee Hunt; Howard Gurney; Monica Tang; Sallie-Anne Pearson; Claire M. Vajdic (Elsevier, 2023)
Summary: Background: Cardiovascular disease (CVD) and cancer are leading causes of death and people with cancer are at higher risk of developing CVD than the general population. Many cancer medicines have cardiotoxic effects but the size of the population exposed to these potentially cardiotoxic medicines is not known. We aimed to determine the prevalence of exposure to potentially cardiotoxic cancer medicines in Australia. Methods: We identified potentially cardiotoxic systemic cancer medicines through searching the literature and registered product information documents. We conducted a retrospective cohort study of Australians dispensed potentially cardiotoxic cancer medicines between 2005 and 2021, calculating age-standardised annual prevalence rates of people alive with exposure to a potentially cardiotoxic medicine during or prior to each year of the study period. Findings: We identified 108,175 people dispensed at least one potentially cardiotoxic cancer medicine; median age, 64 (IQR: 52-74); 57% female. Overall prevalence increased from 49 (95%CI: 48.7-49.3)/10,000 to 232 (95%CI: 231.4-232.6)/10,000 over the study period; 61 (95%CI: 60.5-61.5)/10,000 to 293 (95%CI: 292.1-293.9)/10,000 for females; and 39 (95%CI: 38.6-39.4)/10,000 to 169 (95%CI: 168.3-169.7)/10,000 for males. People alive five years following first exposure increased from 29 (95%CI: 28.8-29.2)/10,000 to 134 (95%CI: 133.6-134.4)/10,000; and from 22 (95%CI: 21.8-22.2)/10,000 to 76 (95%CI: 75.7-76.3)/10,000 for those alive at least 10 years following first exposure. Most people were exposed to only one potentially cardiotoxic medicine, rates of which increased from 39 (95%CI: 38.7-39.3)/10,000 in 2005 to 131 (95%CI: 130.6-131.4)/10,000 in 2021. Interpretation: The number of people exposed to efficacious yet potentially cardiotoxic cancer medicines in Australia is growing. Our findings can support the development of service planning and create awareness about the magnitude of cancer treatment-related cardiotoxicities. Funding: NHMRC Centre for Research Excellence in Medicines Intelligence, Cancer Institute NSW Early Career Fellowship.